Comparing paired‐stimulus and multiple‐stimulus concurrent‐chains preference assessments: Consistency, correspondence, and efficiency. Issue 4 (28th May 2021) - Basile, Carissa D.; Tiger, Jeffrey H.; Lillie, Madelynn A.
Abstract : Concurrent‐chains preference assessments have been used to assess preferences for leisure activities, teaching strategies, behavioral interventions, and other protracted events. This assessment model involves presenting an array of representative stimuli (e.g., pictures or colored cards), providing participants with an opportunity to select a representative stimulus from the array, arranging access to the associated activity, and then rank‐ordering activities based upon their accumulated selection frequency across trials. The predominant model for presenting stimuli has been one in which all stimuli are presented in arrays simultaneously (i.e., a multiple‐stimulus model). Activities selected repeatedly are identified as highly preferred and are then sequentially removed from the array to determine a preference hierarchy. The current study compared this approach with an alternative in which representative stimuli were presented to participants in paired arrays. Assessments conducted in the paired‐array format were completed more rapidly than the multiple‐stimulus format with a high degree of correspondence between preference rankings generated by both approaches.